Bidentate Ru(ii)-NC complexes as catalysts for the dehydrogenative reaction from primary alcohols to carboxylic acids. Issue 24 (28th May 2019) - Gong, Dawei; Hu, Bowen; Chen, Dafa
Abstract : Complex1 is active for alcohol dehydrogenative reactions, and two critical intermediates were isolated and characterized. Abstract : Four Ru(ii )-NC complexes were synthesized by one-step processes from the corresponding NC ligands with RuHCl(CO)(PPh3 )3 . These complexes were tested as catalysts for alcohol dehydrogenative reactions, and complex (C5 H4 N)-(C6 H4 )RuCl(CO)(PPh3 )2 (1 ) showed the highest activity. With KOH as the nucleophile and 0.5 mol% catalyst loading, a series of carboxylic acids were synthesized in toluene without any oxidant. Catalyst1 could be transformed to complex (C5 H4 N)-(C6 H4 )RuH(CO)(PPh3 )2 (6 ) when treated with KOH and benzyl alcohol. Complex6 further reacted with PhCHO and H2 O to generate product (C5 H4 N)-(C6 H4 )Ru(OCOPh)(CO)(PPh3 )2 (7 ). Complexes6 and7 exhibited similar efficiency to complex1, suggesting that they can be regarded as the catalytic intermediates of1 .